2005
DOI: 10.1111/j.1365-2133.2005.06484.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with topical methyl aminolaevulinate for 'difficult-to-treat' basal cell carcinoma

Abstract: MAL PDT is an attractive option for 'difficult-to-treat' BCC. Because of the excellent cosmetic results, the treatment is particularly well suited for lesions that would otherwise require extensive surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
113
4
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 21 publications
(34 reference statements)
11
113
4
7
Order By: Relevance
“…Moreover, because PDT is a noninvasive procedure causing minimal damage to surrounding tissue, it offers advantages over excision surgery, particularly for the treatment of lesions in cosmetically sensitive areas, such as the face. [1][2][3] However, long-term follow-up data of controlled clinical trials of topical PDT vs excision surgery (regarded as the treatment of choice for nodular BCC) 4,5 are lacking. We performed a prospective, randomized, multicenter study of simple excision surgery vs topical PDT, using methyl aminolevulinate, a drug showing highly selective uptake by malignant cells, 6 in the treatment of primary nodular BCC.…”
mentioning
confidence: 99%
“…Moreover, because PDT is a noninvasive procedure causing minimal damage to surrounding tissue, it offers advantages over excision surgery, particularly for the treatment of lesions in cosmetically sensitive areas, such as the face. [1][2][3] However, long-term follow-up data of controlled clinical trials of topical PDT vs excision surgery (regarded as the treatment of choice for nodular BCC) 4,5 are lacking. We performed a prospective, randomized, multicenter study of simple excision surgery vs topical PDT, using methyl aminolevulinate, a drug showing highly selective uptake by malignant cells, 6 in the treatment of primary nodular BCC.…”
mentioning
confidence: 99%
“…Data from other studies support that PDT leads to better cosmetic results compared to surgical excision [81,82]. Also PDT serves as an effective alternative treatment option in difficult cases where an extensive surgical excision should have been performed carrying the risk of a worse cosmetic outcome [84].…”
Section: Basal Cell Carcinomamentioning
confidence: 97%
“…Several prospective studies have demonstrated the efficacy and safety of MAL-PDT in the treatment of superficial and nodular BCCs [6,7,8,9,10]. Yet, in analogy to other destructive and non-histology-controlled treatments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For BCCs, the primary endpoint of most clinical studies has been the complete response rate [6,7,8,9,10]. However, no study has focused on those BCCs recurring after PDT.…”
Section: Introductionmentioning
confidence: 99%